A cluster-based strategy for scheduling task on heterogeneous processors - Boeres, C.; V. Filho, J.; Rebello, V. E. F. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2004)
Efficient task scheduling is fundamental for parallel applications to achieve good performance on distributed systems. While extensive work exists for scheduling tasks on homogeneous processors, fewer algorithms exist for the more common problem of scheduling in heterogeneous processor environments. In this paper, we propose coupling a replication-based clustering heuristic for homogeneous processors, with a mechanism to map the generated clusters to the heterogeneous environment. Experimental results show that this strategy compares favourably in terms of the makespan with traditional list scheduling approaches to this problem, particularly when communication costs are high.